2016
DOI: 10.17707/agricultforest.62.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Biological Studies on the African Fig Fly, Zaprionus Indianus Gupta (Diptera: Drosophilidae)

Abstract: SUMMARYThe African fig fly, Zaprionus indianus Gupta, is a widely distributed polyphagous drosophilid fly of tropical origin. Its occurrence in Jordan was first reported on date palms from the Central Jordan Valley in June 2012. Studies on biological aspects of a fly population collected from Northern Jordan Valley were carried out under laboratory conditions at 25±1˚C, 75±10% RH, and 14 h photoperiod. Mashed banana fruits with dry active yeast of Saccharomyces cerevisiae were used for the first time as a diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The number of generations per year varies from 12 to 16 (Karan et al., 2000; Setta and Carareto, 2005; Nava et al., 2007). Field and laboratory studies on Indian populations showed that Z. indianus overwinters in the egg stage and to a small extent as pupae (Alawamleh et al., 2016).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…The number of generations per year varies from 12 to 16 (Karan et al., 2000; Setta and Carareto, 2005; Nava et al., 2007). Field and laboratory studies on Indian populations showed that Z. indianus overwinters in the egg stage and to a small extent as pupae (Alawamleh et al., 2016).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…The implementation of effective techniques for monitoring and controlling populations is essential to manage crop pests (Alawamleh et al., 2016; Montgomery et al., 2021). Chemical control is a commonly used technique, but its excessive use can lead to the development of resistance (Hu, 2020).…”
Section: Introductionmentioning
confidence: 99%